Motivation for Learning English Early Childhood Through Storytelling Method Using e-Big Book Media - Diantari, Ni Made Eva; Tirtayani, Luh Ayu (Universitas Pendidikan Ganesha, 2020)
English learning motivation is a condition that arises in a person to carry out learning activities, especially English, to increase vocabulary and achieve learning goals, but the learning process was still focused on the teacher and used lecturing method. Therefore, this research aimed to analyze the use of storytelling methods based on e-big book media. This research was a quasi-experimental research with nonequivalent control group design. The population of this research was group B which was consisted of 546 children. The samples were taken by a cluster random sampling technique. The sample consisted of 25 students in the experimental group and 22 students in the control group. Data collection was done by using a non-test with an observation method. The data were analyzed by using t-test. The results of data analysis were t-count = 10,73 at the 5 % significance level and dk = 45, t-table = 2,003 t-count = 10,73> t-table = 2,003. So, the use of storytelling methods based on e-big book media would have an impact on English learning motivation. This research helps teachers to add references to learning media that can be used.